An Analysis Auditor Switching Determinants of Property and Real Estate Companies Listed on the Indonesia Stock Exchange - Melisara Br Pinem; Puja Rizqy Ramadhan; Rahima Br Purba (Economit Journal: Scientific Journal of Accountancy, Management and Finance, 2022)
This paper aims to examine and analyze the effect of the size of the Public Accounting Firm (KAP), audit opinion, and leverage, on auditor switching. This research was conducted using associative research using secondary data. The population in this study were all property and real estate companies listed on the Indonesia Stock Exchange in 2016-2020, totaling 54 companies. With purposive sampling, the sample that met the criteria in this study was 42 companies with a total of 210 observations. Processing of data using logistic regression test based on testing dummy variables. The results of this study prove that partially KAP size has a significant effect on auditor switching, while audit opinion and leverage have no significant effect on auditor switching.